Can laser irradiation improve the strength of weak rock mass? - Xiaowei Feng; Peng Huang; Valter Carvelli; Gongshun Lin; Chuankai Zhu; Fengzhen He (Journal of Rock Mechanics and Geotechnical Engineering)
Controllable rock cracking technology is crucial for the exploration and exploitation of deep underground resources. Many existing studies have been dedicated to the laser-assisted rock-weakening technology. It has been proved that laser irradiation can improve drilling and blasting efficiency when combined with mechanical rock fracturing methods, which are irrelevant for borehole stabilization. To improve the latter, this study used laser ablation for borehole reinforcement. The high-power laser was applied to typical rock samples (sandstone, mudstone and coal) in both dry and saturated conditions. Multi-technique observations and measurements were used to fully understand the peculiar modifications of the specimens under laser treatment, i.e. mechanical loading, acoustic emission (AE) monitoring, digital image correlation (DIC) strain field evaluation, infrared thermography (IRT) monitoring and X-ray computed tomography (CT) scanning. The results showed that, in addition to the effects already demonstrated, laser irradiation can improve the strength of the soft rock, especially in the saturated state. The process involved a complicated phase change including melting and evaporation of the matrix under high-temperature and high-pressure to form a glassy high strength silicate material. This process is similar to the reaction between molten lava and water, or the impact of an asteroid on the earth. Inspired by the results, a conceptual path for a new borehole stabilization technology using laser ablation was outlined.